ERGONOMIC ANALYSIS OF JOBS IN OFFICE IN A FINANCIAL INSTITUTION (Fiep Bulletin - online, 2013)
This study presents an ergonomic analysis performed on a financial institution based in the city of Curitiba, which was in the process of exchanging your furniture jobs. However, the objective was to analyze whether the exchange of securities of the financial institution may be a factor in disease reduction work. Therefore it was necessary to perform comparative ergonomic workstations with antique furniture and furnishings of the new standard. In addition to checking whether a simplified way to use notebooks exerts direct influence on the ergonomic conditions of work according to the standards adopted in the financial institution. Altogether 30 questionnaires were conducted with workers, 15 for the old standard and 15 for the new standard. To verify the adequacy ergonomic was used the norm NR-17, was also performed comparative analysis of the results to verify improvements and major causes. We conclude that with the modification of the securities could change the condition of ergonomic computer workstation from good to great, which can later be proven with the results of the questionnaires, which showed a reduction of 67% to 27% of complaints back pain, neck, head, arms or legs by workers who are already using the new standard. It was also concluded that the main factor of the improvement occurred by changing the ergonomic seat, and thus further studies can be conducted to verify the reduction of business costs with diseases of work and labor as justification for the exchange of securities of posts computerized work by more sophisticated components that bring better ergonomic conditions for workers.
Keywords: Ergonomic Analysis; Safety; Financial Institutions; Diseases of work.